Population Kinetics and Mechanistic Aspects of Saccharomyces cerevisiae Growth in Relation to Selenium Sulfide Nanoparticle Synthesis - Asghari-Paskiabi, Farnoush; Imani, Mohammad; Eybpoosh, Sana; Rafii-Tabar, Hashem; Razzaghi-Abyaneh, Mehdi (Frontiers in Microbiology, 2020)
Biosynthesis of nanoparticles by microorganisms is a cost- and energy-effective approach. However, how the production of nanoparticles affects the population of producing organism remains as an unresolved question. The present study aimed to evaluate the kinetics of Saccharomyces cerevisiae growth in relation to synthesis of selenium sulfide nanoparticles by using a population model. To this end, the population of S. cerevisiae cells was investigated in terms of colony forming units (CFU) in the presence of the substrate in different time points. Fluctuation of sulfite reductase activity, expression of MET5 and MET10 genes, and concentrations of sulfite and selenium were evaluated to support the population findings. CFU values in the test groups were lower than those in the control counterparts. The rise and fall of the sulfite reductase activity and MET5 and MET10 gene expression conformed to the variations of CFU values. The rate of reduction in the selenium and sulfite concentrations tended to decrease over the time. In conclusion, the cells population was negatively and positively affected by selenium and sulfite concentrations, respectively. The indirect relationship of the selenium ions concentration in the path analysis revealed that the product, selenium sulfide nanoparticles, caused this drop in S. cerevisiae cells population.